Pseudostatic analysis for seismic slope stability of dike - Chong, Wan Yoon. (2013)
This report describes a pseudostatic analysis for seismic slope stability of dike with simulation study using PLAXIS 2D Finite Element Program and GeoStudio SLOPE/W analysis. Much focus is given to the comparison of factor of safety of the dikes obtained from 84 dike models created using these two programs, with variation being made on the seismic coefficient and ground water level of the model.